Forest landscape nomination in the Komi-Permyatsky language - Anatoly N. Rakin (Финно-угорский мир, 2020)
Introduction. The article discusses the nomination of the forest landscape in the Komi-Permyatsky language, a separate microsystem, as a part of the terrestrial landscape vocabulary. It has its own structural organization, certain composition of nomination objects and a specific set of lexical means for their nomination. The purpose of the article is to establish systemic features typical for this category of nomination only, distinguish it from other components of land vocabulary, determine the composition of the vocabulary, systematize this microsystem and identify the sources and main stages of its formation and development. Materials and methods. The main source of the material was the vocabulary of the Komi-Permyatsky language contained in lexicographic publications. Additional data was obtained as a result of a survey of native speakers of the Komi-Permyatsky language using a specially developed questionnaire. It also used comparative, historical, synchronous-comparative, descriptive and statistical research methods. Results and discussion. As a result of the linguistic analysis, a system for the forest landscape nomination in the Komi-Permyatsky language is presented. It is established that unambiguous and ambiguous names are distinguished at the semantic level among nominative units, which, as a rule, have a direct meaning. Based on the subject-conceptual content, the entire set of nominations, in accordance with denotative signs, is classified into six main subgroups. The primordial fund of the microsystem is characterized by the presence of all four components of ancient vocabulary: Pre-Perm, Common Perm, Pracomi and the proper Komi-Permyatsky. A part of the native vocabulary that arose during the period of the independent existence of the Komi-Permyatsky language and which does not have genetic correlations with other related languages is analyzed taking into account the specific features of structural and word-building system. As a classification criterion for monomial tokens, it employs the derivative or non-derivative criteria of the words. For compound names it employs the belongings of the components to the corresponding parts of speech. A foreign vocabulary of Komi-Permyatsky words used for the forest landscape consists of one type of borrowing. Conclusion. The vocabulary of the forest landscape of the Komi-Permyatsky language has ancient origins; its formation and development proceeded over many millennia on the basis of internal resources. The number of borrowings increased in the late periods of the Komi-Permyatsky language as a result of the penetration of the corresponding number of words from the Russian literary language and its northern dialects.